Event History Analysis : a Process Point of View. - Aalen, Odd O. (Statistics for biology and health., 2008)
Demonstrates how counting processes, martingales, and stochastic integrals fit nicely with censored data. This book shows how dynamic path analyses can incorporate many modern causality ideas in a framework that takes the time aspect seriously. It includes examples from medicine. It is intended for investigators who use event history methods.